Basic issues in reforming social security systems - Francisco Eduardo Barreto de Oliveira (Institute for Applied Economic Research (ipea), 2015)
The paper analyses conceptual issues involved in the design and/or reform of social security systems classified in three major groups: general characteristics, costing and operational issues.
Keywords: 330